Liver Transplantation for Unresectable Calcifying Nested Stromal Epithelial Tumor: Case Report With a 1-Year Follow-Up and Review of Literature - Kruk, Emilia; Kobryń, Konrad; Rykowski, Paweł; Szczepankiewicz, Benedykt; Patkowski, Waldemar; Zieniewicz, Krzysztof (Frontiers in Surgery, 2022)
Introduction: Calcifying Nested Stromal Epithelial Tumor (CNSET) is an extremely rare diagnosis among patients treated for primary hepatic neoplasms. There are only 45 cases reported worldwide. Histopathological characteristics are well demarcated nests of spindle and epithelioid cells in a dense desmoplastic stroma with variable calcification and ossification. It is mostly diagnosed in children and young females. Treatment strategies implemented for management of CNSET include radiofrequency ablation, transarterial chemoembolization, surgical resection, adjuvant and neo-adjuvant chemotherapy and liver transplantation. Given small number of available cases there are still no established standards of treatment for this neoplasm. Case presentation: A 28-year-old female diagnosed with CNSET presented mild abdominal pain, with normal laboratory values. The tumor was initially deemed unresectable, therefor the patient was disqualified from liver resection. Further deterioration of the patient clinical condition and local tumor progression led to qualification for liver transplantation. The patient underwent liver transplantation one year following initial diagnosis and a twelve months recurrence-free period was observed. During the course of treatment, she did not receive systemic chemotherapy, radiotherapy, nor loco-regional treatment. Conclusion: Multiple strategies have been implemented for treatment of CNSET, liver resection providing the best outcomes. Transarterial chemoembolization, radiofrequency ablation and radiotherapy are reported to be insufficient in management of this tumor. Various chemotherapy regimens turned out to be ineffective as well. There have been only 8 reported cases of patients undergoing liver transplantation for CNSET, with tumor recurrence in two cases. CNSET appears to be a neoplasm with low malignancy potential, although an aggressive progression has subsequently been reported. Further investigation is still required in this field.